Pregnancy-related complications in patients with endometriosis in different stages - Khadijeh Shadjoo; Atefeh Gorgin; Narges Maleki; Arash Mohazzab; Maryam Armand; Atiyeh Hadavandkhani; Zahra Sehat; Aynaz Foroughi Eghbal (BMC, 2024)
Abstract Background Endometriosis is one of the most common and costly diseases among women. This study was carried out to investigate pregnancy outcomes in women with endometriosis because of the high prevalence of endometriosis in reproductive ages and its effect on pregnancy-related complications outcomes. Methods This was a cross-sectional study performed on 379 pregnant women with endometriosis who were referred to the endometriosis clinic of the Avicenna Infertility Treatment Center from 2014 to 2020. Maternal and neonatal outcomes were assessed for the endometriosis group and healthy mothers. The group with endometriosis was further divided into two groups: those who underwent surgery and those who either received medication alone or were left untreated before becoming pregnant. The analysis of the data was done using SPSS 18. Results The mean age of the patients was 33.65 ± 7.9 years. The frequency of endometriosis stage (P = 0.622) and surgery (P = 0.400) in different age groups were not statistically significant. The highest rates of RIF and infertility were in stages 3 (N = 46, 17.2%) (P = 0.067), and 4 (N = 129, 48.3%) (P = 0.073), respectively, but these differences were not statistically different, and the highest rate of pregnancy with ART/spontaneous pregnancy was observed in stage 4 without significant differences (P = 0.259). Besides, the frequency of clinical/ectopic pregnancy and cesarean section was not statistically different across stages (P > 0.05). There is no significant relationship between endometriosis surgery and infertility (P = 0.089) and RIF (P = 0.232). Most of the people who had endometriosis surgery with assisted reproductive methods got pregnant, and this relationship was statistically significant (P = 0.002) in which 77.1% (N = 138) of ART and 63% (N = 264) of spontaneous pregnancies were reported in patients with endometriosis surgery. The rate of live births (59.4%) was not statistically significant for different endometriosis stages (P = 0.638). There was no stillbirth or neonatal death in this study. All cases with preeclampsia (N = 5) were reported in stage 4. 66.7% (N = 8) of the preterm labor was in stage 4 and 33.3% (N = 4) was in stage 3 (P = 0.005). Antepartum bleeding, antepartum hospital admission, preterm labor, gestational diabetes, gestational hypertension, abortion, placental complications and NICU admission were higher in stage 4, but this difference had no statistical difference. Conclusion Endometriosis is significantly correlated with infertility. The highest rates of RIF and infertility are observed in stages 3 and 4 of endometriosis. The rate of pregnancy with ART/spontaneous pregnancy, preterm labor, preeclampsia and pregnancy-related complications is higher in stage 4. Most of the people who had endometriosis surgery with assisted reproductive methods got significantly pregnant. Clinical/ectopic pregnancy, cesarean sections, and live birth were not affected by the endometriosis stages.